2020
DOI: 10.1038/s41598-020-68145-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the sensitivity of single band ratiometric luminescent nanothermometers based on Tb3+ ions through activation of the cross relaxation process

Abstract: the description of luminescent processes and their thermally induced changes, that may be also influenced by the optically active ions concentration, and thus by the various inter-ionic processes, is the key to the improved development of luminescence thermometry. A phosphor doped with only trivalent terbium ions was described, which, by using two excitation lines fitted to the 7 f 6 → 5 D 3 and 7 f 5 → 5 D 3 transitions, shows a luminescent signals with the opposite characteristics of intensity changes as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The energy gap between the 5 D 4 level and the lower 7 F 0 level was high enough (~15 000 cm −1 ) to hinder its multiphonon relaxation, [ 47 ] then the W ph rate was also expected to be negligible. As 5 D 4 lifetime is experimentally constant, this eliminates concentration quenching (W q ) rate and, therefore, we could conclude that the experimentally observed lifetime should be close to the 5 D 4 radiative lifetime τ exp = τ rad .…”
Section: Resultsmentioning
confidence: 99%
“…The energy gap between the 5 D 4 level and the lower 7 F 0 level was high enough (~15 000 cm −1 ) to hinder its multiphonon relaxation, [ 47 ] then the W ph rate was also expected to be negligible. As 5 D 4 lifetime is experimentally constant, this eliminates concentration quenching (W q ) rate and, therefore, we could conclude that the experimentally observed lifetime should be close to the 5 D 4 radiative lifetime τ exp = τ rad .…”
Section: Resultsmentioning
confidence: 99%
“…KLaP 4 O 12 phosphors with different concentrations of Pr 3þ dopant substituting La 3þ ions, were synthesized using the coprecipitation method described by the authors earlier. [9,21,41] X-ray diffraction studies were carried out using a PANalytical X'Pert Pro diffractometer equipped with an Anton Paar TCU 1000 N temperature control unit using nickel-filtered Cu Kα radiation (V ¼ 40 kV, I ¼ 30 mA). TEM images were taken using Philips CM-20 SuperTwin TEM microscope.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon was investigated both as a function of temperature, which activated the change of the particular energy states population, but also as a function of the dopant ion concentration and its influence on the thermally induced energy transfer in the Pr 3+ ‐doped systems. From the previous research of our group on Tb 3+ , [ 9,21 ] the highest dopant ion concentrations were expected to be optimal for Pr 3+ ions just like in the Tb 3+ ions case—however, it turned out that due to many possible CR processes, the optimal concentration for Pr 3+ ions is not so obvious. In previous modeling, [ 9,21 ] we have also shown that crystal matrices showing high‐energy phonons and a sufficient electron–phonon coupling should be beneficial for SBR thermometry.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations